Vigilância socioassistencial: travessia entre o texto normativo regulamentário e o contexto vivido - Fiorotti, Marlene Rosa de Oliveira (2020)
The present study, conducted as a doctoral dissertation at the Pontifical University of Rio Grande do Sul (PUCRS) in the field of Social Work, aims reflect on the social-assistance vigilance (SAV) and its importance when it comes to the rights of social protection. For that, we aim to unveil some contradictions in the social-assistance vigilance implementation in the municipalities of greater Porto Alegre, in the state of Rio Grande do Sul, Brazil. We have conducted this research in face of the social assistance policy normalization, which presents a weakness in the methodological operating field. One of these fragilities is the non-usage of the five social securities as a measurement in the three social assistance policy’s roles. Our dissertation is characterized as a qualitative research based on the dialectical-critical method. Based on this study, we noted the SAV is, at large, being implemented in the cities by workers’ initiative, all of them associated to the execution of the services. Regarding workers’ understanding, we found that there are understandings referring to SAV as a moral control of the workers and the execution of services, or SAV as the mapping of vulnerability, such as Service Registry, and others. It was possible to note that a hardship of comprehension in relation to SAV and how it takes place in the city has been more present along with workers and outsourced equipment, as well as along with social assistance city board. We have found that the meaning of SAV function in social assistance refers to the interpretation and translation of a reality based on this policy on the perspective of social protection and deprotection, having as its main indicators the five social assistance safe aspects: welcoming; income; conviviality or family, community, and social living; leadership development; and support and help. In this sense, we understand SAV and its macroactivities, studied in the present research, as possible mediators (with their breakthroughs and limitations) in the SAV implementation process. We have also noted the lack of recognition of SAV macroactivities and a lack of data collected as strategic information throughout the municipalities considered. We have also observed a contradiction relating to how social assistance policy is understood, based on the rights and their amplification, as a preventive, protective and proactive social support, since in service’s routine the interpretation given to reality does not offer indicators in the perspective of population autonomy, that is, the right in the place of benefits, and inequality in the place of necessity. This reframing will also impact in the SAV operationalization.